Vertebral Artery Patency and Thrombectomy in Basilar Artery Occlusions: Is There a Need for Contralateral Flow Arrest?. Issue 2 (February 2019) - Boeckh-Behrens, Tobias; Pree, David; Lummel, Nina; Friedrich, Benjamin; Maegerlein, Christian; Kreiser, Kornelia; Kirschke, Jan; Berndt, Maria; Lehm, Manuel; Wunderlich, Silke; Mosimann, Pascal J.; Fischer, Urs; et al.
Abstract : Background and Purpose—: Factors influencing recanalization success in basilar artery occlusions are largely unknown. Preliminary evidence has suggested that flow arrest in the vertebral artery contralateral to the catheter bearing vertebral artery may facilitate recanalization. The aim of this analysis was to assess the impact of anatomic variations and flow conditions on recanalization success in basilar artery occlusion treated with mechanical thrombectomy. Methods—: Consecutive basilar artery occlusions treated with second-generation thrombectomy devices at a single-center were retrospectively analyzed. Baseline patients' characteristics, occlusion length, collateral circulation, underlying stenosis, incomplete occlusions, and patency of the vertebral arteries were analyzed with regards to recanalization success. Aplastic or hypoplastic vertebral artery contralateral to the catheter position was defined as contralateral low flow condition. Logistic regression analysis was used to examine the association between anatomic variations and flow conditions in relation to complete recanalization and the modified Rankin Scale score while controlling for several potentially confounding variables. Clinical impact was evaluated using the modified Rankin Scale score of ⩽3. Results—: One hundred fifteen patients were included (mean age 71.5±12.8, m:f=2:1, median National Institutes of Health Stroke Scale =15, interquartile range =10–22). Complete recanalization was more often observed in patients with contralateral low flow conditions (80.6% versus 50.0%), which remained an independent predictor of complete recanalization in multivariable analysis (adjusted odds ratio, 5.81; 95% CI, 1.97–17.19). Patients with complete posterior recanalization had lower in-hospital mortality (16.4% versus 41.7%) and more often achieved modified Rankin Scale score of ⩽3 (49.4% versus 8.3%), even after adjusting for potential confounders (adjusted odds ratio, 15.93; 95% CI, 1.42–179.00). Conclusions—: Contralateral low flow condition (vertebral artery aplasia or hypoplasia) seems to be an independent factor for fewer distal emboli and complete recanalization in basilar artery occlusion patients treated by modern endovascular devices. Complete recanalization reflecting the absence of peri-interventional clot fragmentation brings clear clinical benefit. Further studies are warranted to evaluate the need for contralateral flow modulation or ipsilateral balloon guide catheter during posterior circulation thrombectomy in patients with bilaterally patent vertebral arteries. Abstract : Supplemental Digital Content is available in the text.